A new species of the ant-hunter genus Tracheliodes Morawitz (Hymenoptera: Crabronidae: Crabronini) from Brazil - Melo, Gabriel A. R.; Rosa, Brunno B. (Zootaxa, 2015)
Tracheliodes leclercqi sp. n., a new species of the ant-hunter genus Tracheliodes Morawitz, is described from southeastern Brazil. It closely resembles T. cutucu Cooper, 1988 and the main differences between the two species are presented. Photographs of type specimens of T. leclercqi sp. n., as well as of a female and a male paratypes of T. cutucu, are provided.